Tinjauan Viktimologis Tentang Peranan Korban dan Perlindungan Hukum bagi Korban dalam Terjadinya Kekerasan pada Masa Pacaran di Kota Kupang - Andreas F. Ratoe Oedjoe; Aksi Sinurat; Deddy R. CH. Manafe (Jurnal Hukum dan Sosial Politik, 2024)
Dating violence is an act of violence against a partner who is not yet married, including physical, psychological and sexual violence. The facts behind the occurrence of cases of violence during the dating period occur due to various causal factors, one of the factors that can cause these acts of violence can be caused by the victims themselves. The impact of violence in courtship is of course that there are parties who suffer both physically and psychologically and are entitled to their rights in the fulfillment and protection of their lives, as well as from psychosocial aspects that greatly affect the psychology and life of individuals and are very influential and reciprocal in the lives of victims, with the fulfillment of victims' rights such as medical treatment, counseling, therapy and rehabilitation, victims can be restored to normal. This study aims to determine the role of victim factors in the occurrence of violence in the dating period, as well as the form of legal protection for victims of dating violence. This research uses empirical legal research methods sourced from data obtained directly in the form of statements and opinions from respondents, namely the perpetrator, the victim, the Office of Women's Empowerment and Child Protection, and the PPA Polresta Kupang Kota. The results showed that the occurrence of violence during the dating period was also caused by the role of the victim, namely the provocation of the victim and the dependence of the victim on the perpetrator, then the results also showed that there was a form of legal protection for victims in the form of providing legal assistance, providing health assistance, spiritual assistance and rehabilitation.